1996
DOI: 10.1002/pssb.2221930206
|View full text |Cite
|
Sign up to set email alerts
|

Cu2(1−z)MnzGa2Se4 alloys: Phase diagram and effects of Mn ordering on magnetic behaviour

Abstract: X-ray powder diffraction, differential thermal analysis, and magnetic susceptibility measurements on polycrystalline samples are used to determine the details of the T ( z ) phase diagram of the alloy system Cu~(l-,~Mn,Ga$3e~. At high temperatures, there is a single phase solid solution across the complete diagram in a disordered zincblende phase. However, at lower temperatures, the singlephase range is limited to relatively wide terminal fields, which are ordered structures based on a ziricblende subcell. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…1a, for a sample with z = 0.9, shows a linear 1/c variation with T over the complete range investigated, with a Curie-Weiss q value of À24 K. The curve in Fig. However, as was shown previously [4,8,9] for alloys of similar phase diagrams, the values of the Curie-Weiss constant q determined from magnetic measurements give a good indication of the ordering of the Mn atoms in the lattice. In this case extrapolation of the linear region of the curve gave a value of q of about À100 K. Analysis and Discussion As indicated above, at low temperatures two single-phase solid fields occur.…”
Section: Sample Preparation and Experimental Techniquessupporting
confidence: 77%
“…1a, for a sample with z = 0.9, shows a linear 1/c variation with T over the complete range investigated, with a Curie-Weiss q value of À24 K. The curve in Fig. However, as was shown previously [4,8,9] for alloys of similar phase diagrams, the values of the Curie-Weiss constant q determined from magnetic measurements give a good indication of the ordering of the Mn atoms in the lattice. In this case extrapolation of the linear region of the curve gave a value of q of about À100 K. Analysis and Discussion As indicated above, at low temperatures two single-phase solid fields occur.…”
Section: Sample Preparation and Experimental Techniquessupporting
confidence: 77%
“…(CuGaTe)(CdTe) [1,6,28,45]; (AgInTe 2 )(ZnTe) [18,28] [24,26,43]; (AgInTe 2 )(MnTe) [14,26,42] (CuGaTe 2 )(MnTe) [16] cubic (NaCl) relative short range of solid solubility (CuInSe 2 )(MnSe) [15]; (CuGaSe 2 )(MnSe) [44]; (CuInS 2 )(MnS) [50] hexagonal (W) short range of solid solubility exceptions: relative large single phase field (CuAlS 2 )(CdS), (CuGaS 2 )(CdS), (CuAlS 2 )(CdS), (AgAlS 2 )(CdS), (AgInS 2 )(CdS), (AgAlS 2 )(ZnS), (CuInS 2 )(CdS), (AgGaS 2 )(CdS) [4,28]; (CuGaSe 2 )(CdSe) [25,28]; (AgGaS 2 )(ZnS) [2,28] ; (AgInS 2 )(ZnS) [2,3,28] (CuInSe 2 )(CdSe) [12,28] usually gives samples showing conditions corresponding to equilibrium near room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have been extended to the investigation of the tetrahedrally coordinated I-III-VI 2 , II-III 2 -VI 4 and I 2 -II-IV-VI 4 compounds and alloys [4][5][6]. Another group of semiconducting materials, which would show similar tetrahedrally bounded form, are the II 2 -IV-VI 4 compounds.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the olivine structure of II 2 -IV-VI 4 inversion symmetry and four on 4c sites with mirror symmetry, giving various magnetic configurations at low temperature. The magnetic properties of the Mn 2 SiS 4 and Fe 2 GeS 4 have been studied by magnetization and neutron diffraction measurements, and it was found that several different magnetic configurations in succession going from helium to room temperature occur in these compounds [10,11].…”
Section: Introductionmentioning
confidence: 99%